Training in Chinese Small Firms - Dai, Zhejun (2007)
The dissertation aims to review the currently predominant literature on the factors influencing the training in small business in the industrialized Western economies and to carry out empirical investigation on the determinants of training in Chinese small business and then analyze whether the Western-based literature is consistent with the practices of training in Chinese small firms. In addition, relevant problems with training in small business are presented and recommendations on how to resolve those problems are put forward in order to achieve a better performance in small business sector.